Immune complexome analysis of a rich variety of serum immune complexes identifies disease-characteristic immune complex antigens in systemic sclerosis. Issue 134 (January 2023) - Kutsuna, Yuki Jimbayashi; Iwamoto, Naoki; Ichinose, Kunihiro; Aibara, Nozomi; Nakashima, Katsumi; Nakamura, Hideki; Koike, Yuta; Murota, Hiroyuki; Ueki, Yukitaka; Miyamoto, Hirotaka; Hashizume, Junya; Kodama, Yukinobu; et al.
Abstract: Systemic sclerosis (SSc) is an autoimmune disease characterized by vascular endothelial dysfunction and skin fibrosis. Recently, the presence and pathogenic role of immune complexes (ICs) of SSc patients were reported. However, the identities of antigens in these ICs are unknown. Therefore, we examined ICs in the serum of SSc patients to elucidate SSc pathogenesis. In this study, IC concentrations in serum samples from SSc and systemic lupus erythematosus (SLE) patients were measured by C1q enzyme-linked immunosorbent assays; immune complex analysis was used for comprehensive identification and comparison of antigens incorporated into ICs (IC-antigens). The expression patterns of SSc-specific IC-antigens in skin sections were investigated by immunohistochemistry. Compared with SLE patients who developed disease because of IC deposition, SSc patients had a greater number of IC-antigens and a smaller difference in IC concentrations, suggesting that SSc pathogenesis is affected by the proteins present in ICs. In contrast, the IC concentration and number of IC-antigens did not significantly differ according to the clinical phenotype of SSc. We identified 478 IC-antigens in SSc patients, including multiple RNAP II-associated proteins that were targeted by antibodies previously associated with SSc pathogenesis. The most frequently detected RNAP II-associated protein, RNA polymerase II transcription subunit 30 (MED30), was strongly expressed at lesion sites and reportedly regulates endothelial differentiation. Therefore, increased expression of MED30 in lesions may have an antigenic effect, and MED30 function may be impaired or inhibited by IC formation. RNAP II-associated proteins may SSc pathogenesis through mechanisms such as the MED30 pathway. Highlights: A rich variety of antigens forms small numbers of ICs in SSc patients. MED30 was the most frequently and exclusively detected protein in SSc patients. RNAP II-associated proteins may affect SSc pathogenesis.